Management of Irreparable Rotator Cuff Tears with the Graftjacket Allograft as an Interpositional Graft. Issue 3 (June 2013) - Modi, Amit; Singh, Harvinder Pal; Pandey, Radhakant; Armstrong, Alison
Background: The management of irreparable rotator cuff tears in younger patients remains challenging. The results achieved using arthroscopic debridement, tendon allograft and muscle transfers have been unpredictable. Methods: We report a prospective study of 61 patients with irreparable rotator cuff tears who were treated with open cuff reconstruction using the GraftJacket (i.e. acellular human dermal matrix) (Wright Medical Technology, Inc., Arlington, TN, USA) to bridge the defect. The average age at the time of surgery was 62.6 years (range 47 years to 72 years). All patients were evaluated using the Oxford Shoulder Score pre- and postoperatively. The mean follow-up period was 3.6 years (range 1 year to 6 years). Results: There was a significant improvement in the Oxford Shoulder Score from 26.4 to 44.6 ( p < 0.01) after surgery, with a similar improvement in pain score from 7 pre-operatively to less than 1 at follow-up. Significant improvements were also seen in the strength and range of movement. This improvement in function was seen even if pre-operative magnetic resonance imaging (MRI) scans showed > 50% fatty changes. Postoperative MRI scans showed the graft to be in continuity with the tendon. Conclusions: The results obtained in the present study suggest that the GraftJacket allograft regenerative tissue matrix provides a very good option for bridging irreparable rotator cuff tears in the short to medium term.